2004
DOI: 10.1016/j.buildenv.2003.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a radiant heating and cooling model for building energy simulation software

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(53 citation statements)
references
References 5 publications
0
49
0
4
Order By: Relevance
“…Laouadi [62] implemented a semi-analytical model of the RHC system in the energy simulation, where the RHC model is composed of two sets: a one-dimensional numerical model to analyze heat transfer within the building and a two-dimensional analytical model to calculate the heat transfer within the radiant medium, as described in Fig. 4 [62].…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Laouadi [62] implemented a semi-analytical model of the RHC system in the energy simulation, where the RHC model is composed of two sets: a one-dimensional numerical model to analyze heat transfer within the building and a two-dimensional analytical model to calculate the heat transfer within the radiant medium, as described in Fig. 4 [62].…”
Section: )mentioning
confidence: 99%
“…4 [62]. At each timestep, the twodimensional analytical model determines the net heat flux from the radiant system, which is then passed to a user selected node in the one-dimensional floor structure [63].…”
Section: )mentioning
confidence: 99%
“…Scheatzle (2003) presented measured data set for validating simulation tools for radiant/convective systems and concluded that further work is needed to produce a user-friendly radiant/convective system as a package tool, for the thermal simulation of a whole building that can be used by the designers. Numerous studies on modeling radiant heating and/or cooling systems linked to thermal comfort indexes in buildings were presented in Wang et al (2005), Miriel et al (2002, Jones and Chapman KS (1994), Strand and Baumgartner (2005), Ardehali et al (2004), Laouadi (2004), Zmeureanu et al (2003), , Chapman and Zhang (1995), Zhang (1996), andJones (1998).…”
Section: Introductionmentioning
confidence: 98%
“…Des weiteren werden die Grenzen des thermisch aktivierten Bauteils als ideal isoliert (adiabat) angenommen. Die Validierung des Modells nach [9] beschränkt sich auf eine Flächen-kühlung bzw. -heizung für nur einen Raum, [12].…”
Section: Introductionunclassified